4 - Electoral Politics in Zimbabwe: Authoritarianism Versus the People: by John Makumbe - Makumbe, John (Africa Development, 2006)
The majority of Zimbabweans are now accustomed to electoral fraud as practised by the ruling Zimbabwe African National Union-Patriotic Front (ZANU-PF) led by President Mugabe. Elections are generally not conducted in a manner that can be deemed to be free, fair and transparent. The major electoral malpractices include lack of transparency in the electoral procedures, lack of information on electoral regulations among both the electorate and the contestants, numerous amendments to the laws, most of which are aimed at disenfranchising sections of the electorate who are suspected of supporting opposition political parties, and fraudulent tallying of the votes at counting. Political violence also plays a major role in Zimbabwe’s electoral politics. The chief perpetrators of political violence are by far elements within the ruling ZANU-PF party. Human rights groups in Zimbabwe report that the majority of the victims of political violence during election times are members of opposition political parties. Apart from control of the state media for partisan political purposes, the whole electoral machinery is also effectively controlled by President Mugabe himself through direct appointments to them. Even the law-enforcement agencies are loyal to the President and the party. These have created a grossly uneven political playing field, pose a sever security dilemma for political dissenters, and render elections a farcical exercise in democracy.